Latin American Integration and Asymmetric War - Centeno Mena, Reinaldo (2016)
The author shows that Venezuelan geopolitical doctrine rests heavily in a series of assumptions with regards to the abundance of natural resources in Latin America, and the ambitions of the United States.  In this scenario, Venezuelan politics looks for consolidating a series of alliances (CAN, MERCOSUR, ALBA, UNASUR) that are hoped would counterbalance the American power in the region.